1995
DOI: 10.1002/eji.1830250742
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant CD30 ligand and CD40 ligand share common biological activities on Hodgkin and Reed‐Sternberg cells

Abstract: The CD30 ligand (CD30L) and CD40L are members of the tumor necrosis factor (TNF) protein superfamily, CD30L and CD40L are mainly expressed as membrane-bound proteins by activated T cells. CD30L and CD40L are costimulatory for T cell proliferation and activation. Further, CD40L is a critical signal for T cell-dependent activation of B cells. Primary and cultured Hodgkin and Reed-Sternberg (H-RS) cells, the neoplastic component of Hodgkin's disease (HD), express high levels of the counterreceptors CD30 and CD40.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
0

Year Published

1996
1996
2004
2004

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(29 citation statements)
references
References 41 publications
2
27
0
Order By: Relevance
“…14 LFA-3-CD2 and ICAM-1-LFA-1 interactions are thought to play a role in the stimulating capacity of these cell Discussion lines. 14,25 Looking to potential differences between B7-1 and B7-2 in providing the accessory signal, we found that B7-1 B7-1 expression on RS cells was first shown by us 14 and later confirmed by Munro et al 20 and by Gruss et al 21 In this article, was the stronger CD28 ligand for costimulation. This finding is compatible with other data that B7-1 is superior to B7-2 in we have shown that RS cells in all cases of Hodgkin's disease studied also express B7-2 molecules.…”
Section: Immunohistochemical Analysis Of Non-hodgkin's Lymphomasmentioning
confidence: 60%
“…14 LFA-3-CD2 and ICAM-1-LFA-1 interactions are thought to play a role in the stimulating capacity of these cell Discussion lines. 14,25 Looking to potential differences between B7-1 and B7-2 in providing the accessory signal, we found that B7-1 B7-1 expression on RS cells was first shown by us 14 and later confirmed by Munro et al 20 and by Gruss et al 21 In this article, was the stronger CD28 ligand for costimulation. This finding is compatible with other data that B7-1 is superior to B7-2 in we have shown that RS cells in all cases of Hodgkin's disease studied also express B7-2 molecules.…”
Section: Immunohistochemical Analysis Of Non-hodgkin's Lymphomasmentioning
confidence: 60%
“…Furthermore, it was recently suggested that both CD30 ligand and CD40 ligand, which have an important role in IgE synthesis [29,30], may represent redundant critical elements in the cytokine and cell contact-dependent activation network for the pathology of Hodgkin's disease [23].…”
Section: Discussionmentioning
confidence: 99%
“…Several authors have reported the presence of CD40 on Hodgkin and Reed-Sternberg cells (Carbone et al, 1995a;Gruss et al, 1994;O'Grady et al, 1994). The number of cases expressing CD40 varied between 70% and 100% in the di erent studies, with much of this variation attributable to di erences in ®xation and the use of di erent monoclonal antibodies to CD40.…”
Section: Introductionmentioning
confidence: 99%
“…The number of cases expressing CD40 varied between 70% and 100% in the di erent studies, with much of this variation attributable to di erences in ®xation and the use of di erent monoclonal antibodies to CD40. A variety of functional e ects have been demonstrated in the Hodgkin cell lines in response to stimulation with soluble trimeric CD40-ligand (Carbone et al, 1995a;Gruss et al, 1994Gruss et al, , 1995, suggesting that the CD40 on the cell surface is competent to transduce signals following interaction with its ligand.…”
Section: Introductionmentioning
confidence: 99%